Single-phase Inverter in Grid PV Application - Đỗ Đức Trí; Trần Vĩnh Thanh; Trương Thị Bích Ngà; Nguyễn Phan Anh Tuấn (Journal of Technical Education Science, 2024)
Many countries widely use grid-connected solar power systems. Deploying this technology in urban centers is highly practical because it allows the use of the existing grid while bringing the generated energy closer to the point of consumption. The increasing demand for energy as well as environmental impact from traditional energy sources, especially fossil fuels, have made renewable energy sources more popular. Among these, grid-connected inverters are gaining popularity due to their ease of installation, maintenance, and low purchase cost. The method of controlling a grid-connected single-phase inverter typically use of sinusoidal pulse width modulation (SPWM) algorithm in grid synchronization conditions. In addition , the control technique solves the short-circuit (shoot-through) problem by adding dead-time to the switching process of power switches, calculating component selection, analyzing and building control algorithms for grid-connected inverters. Furthermore, small signal analysis is carried out to design a controller for the grid-connected inverter system, ensuring stable and efficient operation of the system. Research results have been verified using PSIM simulation software and an actual prototype.